Socio-emotional competences in Portuguese youngsters: Developing of assessment tools for parents - Pires, H. (2014)
Social Competence (SC): ability to manage behavior, cognition and affection in order to achieve their social objectives (Waters & Sroufe, 1983). Is multifold and involve positive relationships with others; social cognition appropriate to age; deprivation of maladaptive behaviors and effective social skills (Candeias, 2001). Emotional Intelligence (EI): is a cross-section of interrelated emotional and social competencies, skills and facilitators that determine how effectively we understand and express ourselves, understand others and relate with them, and cope with daily demands. (Bar-On, 2006) .